How to Enhance Lecturers’ Speaking Skill? - Fitri Rayani Siregar (English Education : English Journal for Teaching and Learning, 2019)
Speaking is a dominant skill needed by English lecturer to support their teaching learning process. P2B Lecturer (Language Development Center) at IAIN Padangsidimpuan worked with IALF (Indonesia Australia Language Foundation) BALI a Center to develop language for teachers, lecturers, students and the public. P2B and IALF BALI coordinated holding training once in one semester for lecturers to refresh their abilities and knowledge in order to remain in a very good level. One of the mentors or trainers from IALF BALI came and became a mentor for lecturers in a special class. As a result, the effectiveness of the training was indeed very useful for lecturers to be reused in their next class. Many knowledge, methods, techniques, and games (games) are fun to improve the language skills of students and lecturers.